Release of bisphenol A from polycarbonate and polyethylene terephthalate drinking water bottles under different storage conditions and its associated health risk - Wen, Min Yun; Ho, Yu Bin; Tan, Eugenie Sin Sing; How, Vivien (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Introduction: Bisphenol A (BPA) is a controversial plastics ingredient used mainly in the production of polycarbonate plastics (PC) and epoxy resins that widely used nowadays in food and drink packaging. Even though BPA is not involved in polyethylene terephthalate (PET) manufacturing, recent study had reported the present of BPA in PET water bottle. This study was conducted to investigate effects storage conditions on release of BPA from PC and PET bottled water as well as to assess health risks associated with consumption. Methods: Solid phase extraction (SPE) was used to extract the samples, followed by analysis using ultra high performance liquid chromatography with fluorescence detector (UHPLC-FLD). The possibility of developing chronic non-carcinogenic health risk among consumers of bottled water was evaluated using hazard quotient (HQ). Results: Results showed that BPA migrated from PC and PET water bottles at concentrations ranging from 9.13 to 257.67 ng/L and 11.53 ng/L to 269.87 ng/L respectively. Concentrations of BPA were higher in PET bottled water compared to PC bottled water across all storage conditions. Higher storage temperature and longer storage duration increased BPA concentrations in PC and PET bottled water. Concentrations of BPA in bottled water which were kept in a car and were exposed to sunlight were higher than control samples which were stored indoor at room temperature. Conclusion: No significant chronic non-carcinogenic health risks were calculated for daily ingestion of BPA-contaminated bottled water; calculated HQ was less than one.